Ozone - Gay, Kathlyn (New York : F. Watts, 1989)
Discusses the dual problem of too much ozone in the troposphere creating smog and the depletion of the ozone layer in the stratosphere which shields harmful ultraviolet rays.
Includes index.
Bibliography: p. [116]-122.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Senior High School.
8.9
Keywords: Atmospheric ozone -- Environmental aspects -- Juvenile literature; Chlorofluorocarbons -- Environmental aspects -- Juvenile literature; Ozone layer -- Juvenile literature; Air -- Pollution; Ozone layer; Ozone; Air -- Pollution; Ozone